Measuring the risk level of worker discomfort due to computer use using the ROSA method - Nugroho, Zhafif Radithya; Rizka Aulia, Baiq Putri; Firjatullah, Aji Adinata; Annisa, Putri Dwi (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Computer work carried out for long periods of time can increase the risk of musculoskeletal disorders (MSD) in workers. Working posture is important to increase work productivity among workers. Unergonomic posture is one of the main factors causing MSD. This research aims to analyze risks to computer workers using the Rapid Office Strain Assessment (ROSA) method and provide recommendations for improvements to improve work compatibility. The Rapid Office Strain Assessment (ROSA) method is used to determine the risk value of work activities that use computers and sitting posture. The research results obtained showed that office employees were categorized as requiring further assessment and required follow-up action. Office employees have risky working postures and experience muscle complaints. Based on these results, there are several recommendations such as engineering controls and administrative controls.